2021
DOI: 10.35808/ersj/2392
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development as a Factor Differentiating Consumer Behavior: The Case of Poland

Abstract: The study employed the online survey technique. In order to determine the types of consumers, 18 diagnostic variables characterizing consumer behavior in the context of sustainable development, including sustainable consumption, were used. The type extraction was carried out in two steps. The first was a cluster analysis conducted with the hierarchical Ward method with the square of the Euclidean distance, and the second was a non-hierarchical cluster analysis adopting the k-means method. Findings: As a result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…Concerns about the health risk from food consumption is central in the reasoning of the consumers, while hedonistic goals were only reported occasionally. This contrasts with other works that found that the experience of enjoying a better tasting product is an attractive feature for organic products buyers [45] or Slow Food activists [37].…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…Concerns about the health risk from food consumption is central in the reasoning of the consumers, while hedonistic goals were only reported occasionally. This contrasts with other works that found that the experience of enjoying a better tasting product is an attractive feature for organic products buyers [45] or Slow Food activists [37].…”
Section: Discussioncontrasting
confidence: 73%
“…The participants in this study do experience a strong sense of responsibility towards the environment, which has a positive and direct impact on their actual purchase behavior. They perceive themselves as part of the solution, feeling responsible for acting and fostering a change toward more global sustainability, as found in previous studies [36,45,46]. Such individual responsibility connects, then, with sociopolitical aspirations that are manifested through the aim of challenging dominant power structures and building alternative fair, sustainable, and democratic practices in the economy, e.g., by supporting local farms or strengthening short food supply chains [9,35,47].…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…(1) cognitive barriers, (2) the self, (3) social influence, and (4) product characteristics. On the other hand, the impact of the idea of sustainable development on the differentiation of consumer behavior was studied by the team of Maciejewski [20,21]. The conducted research allowed, among all, to determine that the most common sustainable behaviors undertaken by consumers include avoiding overconsumption [22,23], showing concerns about healthy eating, as well as segregating and recycling waste.…”
Section: Theoretical Backgroundmentioning
confidence: 99%